Prevalence of HIV, Syphilis and Hepatitis B in pregnant of primary healthcare of Callao: Prevalencia de VIH, Sífilis y Hepatitis B en gestantes del primer nivel de atención del Callao - Basilio_Rojas, Marlene Raquel (2020)
Objective: To determine the prevalence of HIV, Syphilis and Hepatitis B in pregnant women who received prenatal care in primary health-care facilities of the Ventanilla Health Network, Callao Region. Materials and methods: Descriptive cross-sectional study. The population was made up of pregnant women attended and registered in the “Wawared” Web Platform of primary health-care facilities considered in the study. The sample included 5,185 pregnant women who received prenatal care in the period from January 2019 to June 2020, whose first prenatal care was entered on the Web Platform. Results: The mean age of the sample was 27.69 years (SD = 6.7; Range: 14 to 48), 48.6% (n = 2520) were 25 to 35 years old, 67% (n = 3473) had secondary education, 59.9% (n = 226) were single and 73.1% (n = 3792) were housewives. The mean age of first sexual relationship was 17.3 years (SD = 2.6; Range: 9 to 41), the mean of number of sexual partners was 2.14 men, 55.3% began prenatal control during the first trimester and therefore were screened early. The percentage of pregnant women with a rapid test reactive to Syphilis, HIV and hepatitis B was 1.08% (55/5015), 0.48% (24/4929) and 0.34% (14/4077) respectively. Conclusions: The frequency of pregnant women with HIV and reactive syphilis exceeds the national prevalence, while reactive Hepatitis B occurs in 0.34% of pregnant women. Keywords: Pregnancy; HIV Infections; Syphilis; Hepatitis B, Peru (Source: MeSH, NLM).